Haploidentical transplantation of hematopoietic stem cells - Hamerschlak,Nelson (2016)
SUMMARY Objective: To review and discuss the literature on hematopoietic stem cell transplantation (HSCT) with haploidentical donors in Brazil. Method: Literature review. Results: The haploidentical hematopoietic stem cell transplantations have become a safe option in hematology since the 80s, with the possibility of ex-vivo T-cell depletion. However, its broad use worldwide occurred with the advent of haploidentical nonmyeloablative transplants using in vivo T-cell depletion with the administration of post-transplant cyclophosphamide. The results were encouraging, despite the increased risk of infection and post-transplantation recurrence. Recent publications on acute myeloid leukemia, myelodysplastic syndrome and Hodgkin’s lymphoma have shown similar results among haploidentical, unrelated and related full-match transplants. Obviously, these findings of retrospective studies should be confirmed by clinical trials. Conclusions: Transplantation with haploidentical donor has shown to be feasible in Brazil and the first publications and results are showing encouraging results.